PENINGKATAN HASIL BELAJAR KOGNITIF DAN HARGA DIRI MAHASISWA MELALUI METODE COOPERATIVE LEARNING TIPE JIGSAW - Purnamasari, Vita; Sundari, Sri; Suryandari, Galuh (Universitas Muhammadiyah Yogyakarta, 2016)
Cooperative Learning Jigsaw type is an innovative learning, the five principal elements of cooperative jigsaw can improve learning outcomes, interpersonal skills, self esteem and motivation. The purpose of research to determine the effect of cooperative learning on learning outcomes and self-esteem students Stikes Surya Global Yogyakarta. The research design is Quasy Experimental design of posttest pretest with control group design, research subjects of Stikes Surya Global 2nd semester with total sampling, the number of respondents is 221 students. Data analysis using Wilcoxon Signed Rank Test and Mann Whitney Test. The results showed that there were significant differences between intervention group and control group with P = 0.000 for cognitive learning and P = 0.000 for self esteem. The conclusion of this research is Cooperative Learning Jigsaw improve cognitive and student’s self esteem Stikes Surya Global Yogyakarta.